2015
DOI: 10.1002/eat.22390
|View full text |Cite
|
Sign up to set email alerts
|

Refeeding and weight restoration outcomes in anorexia nervosa: Challenging current guidelines

Abstract: Refeeding patients with AN using a hospital-based, behavioral protocol may be accomplished safely and more rapidly than generally recognized, weight restoring most patients by discharge. Helpful elements may include the program's integrated, step-down structure; multidisciplinary team approach emphasizing group therapy to effect behavior change; and close medical monitoring for those with BMI < 15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
120
1
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(142 citation statements)
references
References 36 publications
14
120
1
4
Order By: Relevance
“…Expected rates of controlled weight gain are generally 0.5-1.4 kg per week. In significantly malnourished patients, nutritional replenishment may precipitate refeeding syndrome, with hypophosphatemia as the hallmark of this complication [37].…”
Section: Long-term Consequences In Adult Womenmentioning
confidence: 99%
“…Expected rates of controlled weight gain are generally 0.5-1.4 kg per week. In significantly malnourished patients, nutritional replenishment may precipitate refeeding syndrome, with hypophosphatemia as the hallmark of this complication [37].…”
Section: Long-term Consequences In Adult Womenmentioning
confidence: 99%
“…Within this group, prescribed calorie level did not change the risk of electrolyte abnormalities associated with refeeding syndrome [11]. Studies have concluded that percent body weight on admissions was more associated with the development of hypophosphatemia than initial calorie prescription [911]. Two small descriptive studies examining patients presenting with a BMI < 12 (ranging in age from 11 to >40 years old) found that these patients could be safely refed with <1200 kcal per day, but did not assess the safety of a higher calorie diet [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Correlational data strongly suggests that higher discharge BMI following hospital-based weight restoration is associated with lower rates of relapse [23][24][25][26]. Although inpatient treatment can be lifesaving, it is expensive and difficult to access [27].…”
Section: Introductionmentioning
confidence: 99%